Decreasing of Cayenne Pepper Quality During Storage in Room Temperature - Anna Sulistyaningrum; Darudryo Darudryo (JURNAL AGRONIDA, 2018)
Cayenne pepper storage at room temperature will cause physical, mechanical,chemical or microbiological damage in short time. In room terperature conditions cayennepepper can only survive for 2-3 days and finally will be decay. The use of packaging canincrease the small chilli storeability, because packaging can reduce the level of exposure toenvironmental changes. This research aims to study the quality changes of cayenne pepperduring storage on room temperature. The results showed that losses of cayenne pepper weightincreased with increasing duration of storage. Cayenne pepper storaged for 8 days causedweight loss of 24.25%. The use of perforated plastic packaging can reduce the weight loss by16.82%, much lower than the control of 31.67%. The pH of chili during the 8-days decreasedwith value of 6.55 while the control was 6.7. The pH experienced decreased of 2.23% fromthe control (without packaged). While the number of colored cayenne pepper increasedduring storage from 40% in control treatment and 60% in the packaging. The use ofperforated plastic packaging provides a higher organoleptic value with a total value of 18which consists of 4.27 color parameters (close to green), texture 4.5 (very close to very hard),4.6 appearance (near very smooth) and freshness 4.63 (approached very fresh).Keywords: chili, storage duration, weight loss, pH, packing